A case of error disclosure: a communication privacy management analysis - Sandra Petronio; Paul R. Helft; Jeffrey T. Child (SAGE Publishing, 2013)
To better understand the process of disclosing medical errors to patients, this research offers a case analysis using Petronios's theoretical frame of Communication Privacy Management (CPM). Given the resistance clinicians often feel about error disclosure, insights into the way choices are made by the clinicians in telling patients about the mistake has the potential to address reasons for resistance. Applying the evidenced-based CPM theory, developed over the last 35 years and dedicated to studying disclosure phenomenon, to disclosing medical mistakes potentially has the ability to reshape thinking about the error disclosure process. Using a composite case representing a surgical mistake, analysis based on CPM theory is offered to gain insights into conversational routines and disclosure management choices of revealing a medical error. The results of this analysis show that an underlying assumption of health information ownership by the patient and family can be at odds with the way the clinician tends to control disclosure about the error. In addition, the case analysis illustrates that there are embedded patterns of disclosure that emerge out of conversations the clinician has with the patient and the patient's family members. These patterns unfold privacy management decisions on the part of the clinician that impact how the patient is told about the error and the way that patients interpret the meaning of the disclosure. These findings suggest the need for a better understanding of how patients manage their private health information in relationship to their expectations for the way they see the clinician caring for or controlling their health information about errors.